A simple damage model for concrete considering irreversible mode‐II microcracks. Issue 11 (8th April 2016) - Yu, Z.; Shan, Z.; Ouyang, Z.; Guo, F.
Abstract: A simple damage model with the concept of mode‐II microcracks on crack wall contributing to the irreversible strains for concrete is developed. By applying the micromechanics method, a microcell‐based damage model is introduced to understand the damage behaviour. Further, by introducing the physical interpretation of the damage variable using thermodynamic method, a novel damage variable (irreversible‐damage variable) is proposed to describe the irrecoverable strains generated by both mode‐II microcracks and irreversible‐frictional sliding. With this methodology, a simple continuum damage mechanics model is developed in which both elastic and irreversible damages are considered. As demonstrated by the comparison with experimental results, the proposed model is characterized by accuracy of solutions, sufficiency of physical sense and convenience of implementation.